2020
DOI: 10.3390/ijms21176035
|View full text |Cite
|
Sign up to set email alerts
|

The Association of dp-ucMGP with Cardiovascular Morbidity and Decreased Renal Function in Diabetic Chronic Kidney Disease

Abstract: We aimed to investigate the possible association of the inactive, dephosphorylated, uncarboxylated matrix Gla protein (dp-ucMGP) with oxidized low-density lipoprotein (ox-LDL) and all-cause/cardiovascular (CV) mortality and renal function in diabetic chronic kidney disease (CKD). Ox-LDL and dp-ucMGP were determined in 66 diabetic CKD patients. All patients were prospectively followed for seven years, or until the occurrence of death, or a composite renal outcome of 30% estimated glomerular filtration rate (eGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…MGP is an extrahepatic vitamin K-dependent protein that could have beneficial effects in critically ill patients as it acts as a calcification inhibitor [ 16 ]. To date, research has mainly focused on its potential involvement in cardiovascular disease and in uremic vascular calcification [ 30 ] and little is known about how its uncarboxylated form (dp-ucMGP) is affected by critical illness and whether it is a potential biomarker for disease or if it is involved in disease progression [ 31 ]. dp-ucMGP has been suggested as a biomarker for cardiovascular disease, and in diabetic chronic kidney disease patients, an increased dp-ucMGP level has been linked to increased mortality [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MGP is an extrahepatic vitamin K-dependent protein that could have beneficial effects in critically ill patients as it acts as a calcification inhibitor [ 16 ]. To date, research has mainly focused on its potential involvement in cardiovascular disease and in uremic vascular calcification [ 30 ] and little is known about how its uncarboxylated form (dp-ucMGP) is affected by critical illness and whether it is a potential biomarker for disease or if it is involved in disease progression [ 31 ]. dp-ucMGP has been suggested as a biomarker for cardiovascular disease, and in diabetic chronic kidney disease patients, an increased dp-ucMGP level has been linked to increased mortality [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, research has mainly focused on its potential involvement in cardiovascular disease and in uremic vascular calcification [ 30 ] and little is known about how its uncarboxylated form (dp-ucMGP) is affected by critical illness and whether it is a potential biomarker for disease or if it is involved in disease progression [ 31 ]. dp-ucMGP has been suggested as a biomarker for cardiovascular disease, and in diabetic chronic kidney disease patients, an increased dp-ucMGP level has been linked to increased mortality [ 30 ]. Cardiovascular disease is typically progressive over several years and might therefore not be regarded as relevant for the ICU population, where the duration of treatment usually ranges from days to weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic CKD patients with plasma dp-ucMGP levels above the median (≥656 pM) had a significantly higher risk for CV events, CV mortality, and all-cause mortality compared to the low dp-ucMGP group [114]. High levels of dp-ucMGP were significantly associated with higher triglycerides (p = 0.03) and C-reactive protein (p = 0.03) levels, CV mortality (p = 0.037), all-cause mortality (p = 0.02), and progression of CKD (p = 0.024) [114].…”
Section: Vitamin K In the Prevention And Therapy Of Vascular Calcification And Cardiovascular Diseasesmentioning
confidence: 93%
“…Diabetic CKD patients with plasma dp-ucMGP levels above the median (≥656 pM) had a significantly higher risk for CV events, CV mortality, and all-cause mortality compared to the low dp-ucMGP group [114]. High levels of dp-ucMGP were significantly associated with higher triglycerides (p = 0.03) and C-reactive protein (p = 0.03) levels, CV mortality (p = 0.037), all-cause mortality (p = 0.02), and progression of CKD (p = 0.024) [114]. Likewise, a prospective study investigating 4275 people (aged 53 ± 12 years, 46.0% male) for 10 years, concluded that plasma dp-ucMGP was associated with total (hazard ratio (HR) = 1.14; 95% CI: 1.10-1.17, p ≤ 0.001) and CV (HR = 1.17; 95% CI: 1.11-1.23, p ≤ 0.001) mortality [121].…”
Section: Vitamin K In the Prevention And Therapy Of Vascular Calcification And Cardiovascular Diseasesmentioning
confidence: 93%
“…A recently conducted prospective study on 66 diabetic CKD patients showed that high plasma dp-ucMGP levels (≥656 pM) were associated with all-cause mortality (Hazard ratio-HR = 2.63, 95% CI = 1.17-5.94, p = 0.02), CV mortality (HR = 2.82, 95% CI = 1.07-7.49, p = 0.037) and progression of CKD (HR = 4.02, 95% CI = 1.20-13.46, p = 0.024) [35]. These data are in agreement with the results obtained from the prospective general populationbased Prevention of Renal and Vascular End-Stage Disease (PREVEND) study which included 4275 participants [36].…”
Section: Vitamin K and Chronic Kidney Diseasementioning
confidence: 99%